(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the use of "Bloom’s taxonomy" in literature classes is considered important from the point of view of classification and systematization of students’ theoretical concepts and knowledge, and the positive aspects of using "Bloom’s taxonomy" in teaching Erkin Vahidov’s epic "Nido" in higher education institutions are detailed.